Do you know your PSMA-tracer? Variability in the biodistribution of different PSMA ligands and its potential impact on defining PSMA-positivity prior to PSMA-targeted therapy - Jan Heilinger; Katrin Sabine Roth; Henning Weis; Antonis Fink; Jasmin Weindler; Felix Dietlein; Philipp Krapf; Klaus Schomäcker; Bernd Neumaier; Markus Dietlein; Alexander Drzezga; Carsten Kobe (EJNMMI Research)
Abstract Background In clinical practice, several radiopharmaceuticals are used for PSMA-PET imaging, each with distinct biodistribution patterns. This may impact treatment decisions and outcomes, as eligibility for PSMA-directed radioligand therapy is usually assessed by comparing tumoral uptake to normal liver uptake as a reference. In this study, we aimed to compare tracer uptake intraindividually in various reference regions including liver, parotid gland and spleen as well as the respective tumor-to-background ratios (TBR) of different 18F-labeled PSMA ligands to today’s standard radiopharmaceutical 68Ga-PSMA-11 in a series of patients with biochemical recurrence of prostate cancer who underwent a dual PSMA-PET examination as part of an individualized diagnostic approach. Results Differences in background activity among different PSMA-PET tracers lead to variations in tumor-to-background ratios (TBR). In [18F]F-DCFPyL-PET, TBR with the liver as the reference organ (TBRliver) was comparable to [68Ga]Ga-PSMA-11-PET, while [18F]F-PSMA-1007-PET and [18F]F-JK-PSMA-7-PET showed significantly lower values. Using the parotid gland as the reference (TBRparotidgland), [18F]F-DCFPyL-PET exhibited significantly higher values, whereas [18F]F-PSMA-1007-PET and [18F]F-JK-PSMA-7-PET were comparable. For the spleen (TBRspleen), [18F]F-JK-PSMA-7-PET was comparable, but [18F]F-DCFPyL-PET and [18F]F-PSMA-1007-PET showed significantly higher and lower values, respectively. An additional Bland-Altman analyses revealed low bias for [18F]F-DCFPyL-PET in TBRparotidgland, whereas significant differences in TBRliver and TBRspleen for the other tracers resulted in higher bias. Conclusion Different PSMA-PET tracers exhibit distinct biodistribution patterns, leading to variations in tumor-to-background ratios (TBR) in reference organs such as the liver, parotid gland, and spleen. Patient selection for PSMA-directed radioligand therapy is currently based on a semiquantitative approach using the liver as a reference region in [68Ga]Ga-PSMA-11-PET. Thus, the use of alternative [18F]-labeled tracers may result in under- or overestimation of a patient’s suitability for therapy. This highlights the importance of a comprehensive understanding of the differences in tracer-specific uptake behavior for accurate decisions regarding PSMA-expression levels. However, as the patient cohort in this study is at earlier disease stages, the generalizability of these findings to later-stage patients remains unclear and requires further investigation.